2013
DOI: 10.1038/jhh.2013.77
|View full text |Cite
|
Sign up to set email alerts
|

Resistant hypertension: patient characteristics, risk factors, co-morbidities and outcomes

Abstract: Among the vast population of hypertensive subjects, between 10 and 15% do not achieve an adequate blood pressure (BP) control despite the use of at least three antihypertensive agents. This group, designated as having resistant hypertension (RH), represents one of the most important clinical challenges in hypertension evaluation and management. Resistant hypertensives are characterized by several clinical particularities, such as a longer history of hypertension, obesity and other accompanying factors, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 41 publications
8
49
2
4
Order By: Relevance
“…Patients with resistant HT are at the end of the line, exposed to a huge cardiovascular risk and facing few options to choose from. A diagnostic workup to exclude secondary forms of hypertension and confirm resistance (observational studies have shown that white coat HT can be detected in one third of patients diagnosed with resistant HT) 82 should be thoroughly conducted and afterward, a therapeutic strategy should be implemented, always including lifestyle counseling, the necessary and recommended adjustments to the antihypertensive regimen and device-based therapies.…”
Section: No 4-is Rdn Safe?mentioning
confidence: 99%
“…Patients with resistant HT are at the end of the line, exposed to a huge cardiovascular risk and facing few options to choose from. A diagnostic workup to exclude secondary forms of hypertension and confirm resistance (observational studies have shown that white coat HT can be detected in one third of patients diagnosed with resistant HT) 82 should be thoroughly conducted and afterward, a therapeutic strategy should be implemented, always including lifestyle counseling, the necessary and recommended adjustments to the antihypertensive regimen and device-based therapies.…”
Section: No 4-is Rdn Safe?mentioning
confidence: 99%
“…14 Thus, ambulatory blood pressure monitoring is recommended in the clinical evaluation of patients with resistant hypertension. 15 Although ambulatory BP monitoring was not performed in our study conducted in primary care setting, the high prevalence of PAD is suggestive of true resistant hypertension. Falsely elevated BP secondary to calcified arteries, that is, pseudohypertension, was probably distinguished from true resistant hypertension, as we excluded patients with clinically manifested cardiovascular or renal disease and diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…left ventricular hypertrophy or chronic kidney disease) as well as a higher prevalence of previous cardiovascular disease were the main clinical features that differentiated resistant from controlled patients. [7][8][9][10] Notably, patients with treatment-resistant hypertension showed a higher prevalence of target organ damage; in particular, they exhibited a higher prevalence of left ventricular hypertrophy, 9,11 albuminuria and decreased glomerular filtration rate, 12,13 more carotid intima-media thickening and carotid plaques, 11 increased endothelial dysfunction as assessed by impaired flow-mediated dilation of the forearm circulation, 14 and increased arterial stiffness. 15 Adverse cardiovascular outcomes thus occurred most commonly in patients with treatment-resistant hypertension.…”
Section: Clinical Significance Of Treatment-resistant Hypertensionmentioning
confidence: 98%